Adaptation to climate change in Afghanistan: Evidence on the impact of external interventions - Asadullah Jawid; Menusch Khadjavi (Economic Analysis and Policy, 2019)
Climate change is a significant obstacle for farmers in the least developed countries like Afghanistan and adaptation support is exceptionally scarce. This paper provides evidence on the impact of the agriculture-related external support on farmers' adaptation to climate change in the Central Highlands of Afghanistan. To this end, we collected primary data from 1434 farmers whom we interviewed across 14 districts in Bamiyan, Ghazni, and Diakundi provinces. We employ quasi-experimental econometric methods, including an endogenous switching regression analysis, to estimate the treatment effects on various adaptation-related outcomes. We find significant impacts of support interventions on the use of improved types of seeds and farmers' access to irrigation water. Further impacts on the risk of flood, economic and financial as well as government and institutional adaptation constraints appear to be significant, but sensitive to the existence of unobserved factors. We conclude that farmers perceived changes in the climate, and most of them tried to adapt by employing measures available to them. The impact of external support has been partially effective in addressing immediate and short-term farming challenges related to climate change and extreme weather events. They, however, have not been effective in treating long-term fundamental climate change-related risks. Based on our analysis of the past treatments and farmers' selfreported priorities, we provide a list of policy recommendations for adaptation to climate change in farming communities in Afghanistan.
Keywords: 330